Peningkatan Keterampilan Menulis Puisi dengan Menggunakan Media Kincir Pintar pada Siswa Kelas VIII SMP Negeri 1 Kahu - Andi Ira; Mayong Mayong; Usman Usman (Indonesian Journal of Social and Educational Studies, 2022)
This study aims to identify and describe the improvement of students poetry writing skills using the smart wheel media. This research is a classroom action research (CAR). The problem that is found in the implementation of this research in general is the lack of skills of class VIII-A students of SMP Negeri 1 Kahu in learning to write poetry texts. shows that the results of the implementation of learning to write poetry texts in class VIII-A students are still low and improvements are needed to improve learning outcomes. The improvement solution offered by researchers to fix problems in learning is the use of smart wheel media in learning to write poetry texts. The results of increased learning in terms of process are indicated by an increase in student activity in the implementation of the results of observing teacher activities in the first cycle of 69,64% and the second meeting of 76,78% of the fourteen assessment indicators. The increase in the results of observation of teacher activities in the second cycle of the first was 89,28% and the second meeting was 96,42% of the fourteen assessment indicators. The results of the observation of student activities in the first cycle of the first meeting were 66,07% and the second meeting was 78,57% of the fourteen assessment indicators. The results of the observation of student activities in the second cycle of the first meeting were 91,07% and the second meeting 98,21% of the fourteen assesment indicators. The improvement in terms of learning outcomes to write poetry texts is indicated by the avarage score of students in cycle I is 61, and the average value of students in cycle II is 78. Thus the use of smart wheel media can improve learing to write poetry in terms of process and results learning.Keywords: improvement, writing poetry, smart wheel media.